2021
DOI: 10.1101/2021.03.26.21254388
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Relationship between teaching modality and COVID-19, well-being, and teaching satisfaction (Campus & Corona): a cohort study among students in higher education

Abstract: Background: After lock-down during the first wave of the COVID-19 pandemic, higher education institutions globally struggled to balance the need for infection control and educational requirements as they prepared to reopen. A particularly difficult choice was whether to offer for in-person or online teaching, since there was little or no empirical research to inform this decision. Norwegian universities and university colleges opted for a hybrid model when they reopened for the autumn semester, with some stude… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…Comparable studies have typically focused on children or the general population 23,24 while studies on mental health issues due to the pandemic that focus on students in higher education are limited survey and interview studies based on convenience sampling and self-reporting of symptoms and are mainly cross-sectional studies conducted in the rst phase of the pandemic. 2,[5][6][7][8][9] In line with other studies on use of health services during the pandemic, we show that the level of mental health consultations was reduced relative to previous years in the spring of 2020. [25][26][27] This nding is, however, in contrast to survey studies that reported higher prevalence than before of psychological distress, including symptoms such as stress, anxiety, sleep pattern disruption, and depressive thoughts, at the beginning of the pandemic.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Comparable studies have typically focused on children or the general population 23,24 while studies on mental health issues due to the pandemic that focus on students in higher education are limited survey and interview studies based on convenience sampling and self-reporting of symptoms and are mainly cross-sectional studies conducted in the rst phase of the pandemic. 2,[5][6][7][8][9] In line with other studies on use of health services during the pandemic, we show that the level of mental health consultations was reduced relative to previous years in the spring of 2020. [25][26][27] This nding is, however, in contrast to survey studies that reported higher prevalence than before of psychological distress, including symptoms such as stress, anxiety, sleep pattern disruption, and depressive thoughts, at the beginning of the pandemic.…”
Section: Discussionsupporting
confidence: 86%
“…[1][2][3][4] Studies mainly based on convenience samples and cross sectional data suggest that the initial shock of the pandemic and the associated restrictions in the spring of 2020 had an adverse impact on students' mental health and well-being. 2,[5][6][7][8][9][10] In contrast, results for the general population are more mixed, and worsened mental health (if any) tend to emerge later in the pandemic. [11][12][13][14] Furthermore, there has been steep increase in mental health symptoms and diagnoses among (particularly female) students prior to the pandemic, sometimes assessed to be sharper than among their non-enrolled peers.…”
Section: Introductionmentioning
confidence: 99%
“…4 , 22 , 29–32 Some studies have reported that students experience a reduced quality of life, academic stress, financial insecurity, and increased levels of physical problems during the pandemic. 22 , 25 , 30 , 33–36 . Blended learning on campus, according to the flipped classroom model, was implemented in most Norwegian universities’ during the autumn 2020.…”
Section: Discussionmentioning
confidence: 99%